Worm propagation modeling in cloud security - Wei ZHANG; Ru-chuan WANG; Peng LI (Tongxin xuebao)
The emergence of cloud security changed the major virus-defensive position from client to network and server group.From the view of the cloud security,a novel worm propagation model,SIR_C(SIR in cloud security),which drives from SIR model was proposed.Based on considering the traditional human countermeasures and the network congestion traffic which is caused by worms and will curb the spread of worms,SIR_C model focused on the analysis of the impact of the degree of cloud security deployment and the information gathering capability on worm propagation model.The simulation results show that SIR_C model was a meaningful attempt to research worm epidemics in cloud security network.